Pengaruh Lama Waktu Perendaman Dengan Air Terhadap Daya Berkecambah Trembesi (Samanea Saman) - Yuli Ardani Lubis; Melya Riniarti; Afif Bintoro (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Well germination process of rain tree seeds will rised the percentation, capacity, and rate of germination. Nevertheless, there are still some obstacles on the germination process due to it dormancy period. Water is one of medium which could be used to break the dormancy period. This research was conducted at Lampung University green house on March 2012. The aim of this research was to investigate the effect of water submerged time to rain tree germination. This research was arrange on Completely Randomized Design (CRD) with 4 treatment and 4 repeatization. The treatments was the submerging time which was 24, 48 and 72 hours. Test of the similarity range were done by Bartlett test while the analysis by analysis of variance, furthermore the comparison of average values were done by the different test (BNJ) with a 5% confidence interval. The results of this research showed that the effect of submerged time of seed rain tree. The effect of submerged time of seed rain tree for 72 hours was the best percentation of germination and germination of seed rain tree at 68,75% and 80,25%. The submerged time did not effect to rate of germination seed rain tree. Keywords: dormancy, germination, rain tree, scaryfication, submerged